2021
DOI: 10.3390/ijms22062941
|View full text |Cite
|
Sign up to set email alerts
|

m5U54 tRNA Hypomodification by Lack of TRMT2A Drives the Generation of tRNA-Derived Small RNAs

Abstract: Transfer RNA (tRNA) molecules contain various post-transcriptional modifications that are crucial for tRNA stability, translation efficiency, and fidelity. Besides their canonical roles in translation, tRNAs also originate tRNA-derived small RNAs (tsRNAs), a class of small non-coding RNAs with regulatory functions ranging from translation regulation to gene expression control and cellular stress response. Recent evidence indicates that tsRNAs are also modified, however, the impact of tRNA epitranscriptome dere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…The accumulated 5’ tRNAs were shown to be able to activate the uncapped translational repressor program [ 58 , 59 ], resulting in reduced protein synthesis [ 58 ]. As a tRNA methyltransferase, TRMT2A can catalyze 5-methyluridine (m 5 U) modification at position 54 of cytoplasmic tRNAs [ 60 ]. TRMT2A knockdown promoted m 5 U54 tRNA hypomodification and enhanced ANG-dependent production of 5’tiRNA-GlyGCC and 5’tiRNA-GluCTC.…”
Section: Regulation Of Tsrna Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulated 5’ tRNAs were shown to be able to activate the uncapped translational repressor program [ 58 , 59 ], resulting in reduced protein synthesis [ 58 ]. As a tRNA methyltransferase, TRMT2A can catalyze 5-methyluridine (m 5 U) modification at position 54 of cytoplasmic tRNAs [ 60 ]. TRMT2A knockdown promoted m 5 U54 tRNA hypomodification and enhanced ANG-dependent production of 5’tiRNA-GlyGCC and 5’tiRNA-GluCTC.…”
Section: Regulation Of Tsrna Productionmentioning
confidence: 99%
“…Furthermore, Pereira M et al found that silencing TRMT2A inhibited global protein synthesis, however, they did not establish whether TRMT2A-induced 5’ tiRNA can directly modulate protein synthesis (Fig. 2A ) [ 60 ]. In pancreatic β-cells, the methylation transferase, TRMT10A, is responsible for methylating guanosine at the tRNA-Gln and tRNA iniMeth position 9 (m 1 G9) [ 61 63 ].…”
Section: Regulation Of Tsrna Productionmentioning
confidence: 99%
“…The size of tRFs can vary between 10–50 nucleotides ( Ma et al, 2021 ; Yuan et al, 2021 ). Since then, more comprehensive naming systems have been proposed for tRFs ( Megel et al, 2015 ; Xie et al, 2020 ; Pereira et al, 2021 ). Among the five categories, tRFs derived from mature tRNAs are more predominant ( Keam and Hutvagner, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of posttranscriptional modifications of parent tRNA has been shown to influence the biogenesis of tRFs ( Pereira et al, 2021 ). Queuosine (Q) modification in the wobble anticodon position of some tRNAs was found to inhibit cleavage by endonuclease Angiogenin and alter the pool of tRFs in human cells ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation